Country Effects on Information Seeking in Global Electronic Networks - Zaheer, Srilata; Zaheer, Akbar (Journal of International Business Studies, 1997)
We examine the existence of country effects on information seeking in response to market volatility, and explore the institutional factors underlying these effects. The empirical setting is the use of an electronic inter-bank network over twelve months by 3,266 banks located in twenty-five countries. We find significant differences across countries in banks' information-seeking behavior in response to market volatility, influenced both by differences in national industry arrangements and by national culture. However, national industry arrangements and national culture influence banks' information seeking in distinct ways.